Influence of kaolin ignition temperature changes on the strength qualities of proppants; IFOST 2012; Vol. 1 - Reshetova A. A. Antonina Aleksandrovna; Vakalova T. V. Tatyana Viktorovna; Govorova L. P. Larisa Pavlovna; Domukhovskaya E. A. (Section 1. Chemical engineering and "Green technology", 2012)
The article describes investigation of the influence of kaolin ignition temperature of 900°C, 980°C and 1100°C on the strength of proppants. It was established that the ignition temperature of kaolin has a significant influence on the strength of the proppant. It was revealed that the ignition of kaolin at a temperature of 980°C and higher temeperatures causes the appearance of poorly crystallized defective mullite - imperfection of the crystal structure. The presence of defective mullite activates the sintering process (consolidation and hardening) of proppant granules, which provides a proppant with higher strength at the same temperatures (1450°C). In this case the active crystallization of cristobalite from the melt during the sintering roasting reduces the total amount of glass phase in the material, which in its turn is beneficial to increase the strength of the proppants.